ANALISIS PENGARUH PERTUMBUHAN EKONOMI TERHADAP TINGKAT KEMISKINAN DI SUMATERA UTARA - Faisal Alviandi Siadari; Darwin Damanik (Universitas Katolik Widya Karya Malang, 2023)
Poverty is a problem in a complex and multidimensional economy. Therefore it is necessary to find a solution to overcome or at least reduce the level of poverty. This study aims to analyze the effect of the level of economic growth on the level of poverty in the province of North Sumatra. The author uses library research instruments, documentation studies, internet browsing, where the data taken is secondary data from related agencies, especially the Central Bureau of Statistics of North Sumatra, and in analyzing the data using a simple linear regression analysis technique. The results of data processing show that economic growth has a negative and significant effect on poverty rates in the province of North Sumatra.